Pinewood and wheat straw bio-oil aqueous phase electrochemical hydrogenation utilising a PtRu/ACC catalyst - Catizane, Cesar; Jiang, Ying; Banks, Scott; Sumner, Joy (Royal Society of Chemistry (RSC), 2025)
Bio-oil from biomass pyrolysis contains a wide range of oxygenated compounds, limiting its direct use as a fuel due to chemical instability and low energy density. This study investigates the application of electrochemical hydrogenation (ECH) as an alternative to the conventional hydrogenation process to upgrade bio-oil derived from wheat straw and pinewood. Experiments were conducted in a two-chamber electrochemical cell, with ECH conditions optimised based on prior research. Platinum–ruthenium on activated carbon cloth (PtRu/ACC) was selected as the catalyst for ECH reactions. The process preferentially reduced phenolic and carbonyl compounds while increasing the concentration of alcohols, as confirmed by gas chromatography-mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FTIR) analyses. The ECH study revealed substantial reductions in phenolic compounds, notably p-cresol (62.1%) and phenol (29.3%), alongside an increase in alcohol content from 49.3% to 56.5% in pinewood-derived bio-oil. These chemical transformations demonstrate ECH's potential as a milder, more sustainable alternative to traditional hydrodeoxygenation processes. This study provides insights into the ECH process and suggests future directions for optimising bio-oil upgrading and supporting the development of renewable fuels.
Keywords: 34 Chemical Sciences; 3406 Physical Chemistry; 40 Engineering; 4004 Chemical Engineering; 4008 Electrical Engineering; 7 Affordable and Clean Energy